Utilizing the Heliophysics/Geospace System Observatory to Understand Particle Injections: Their Scale Sizes and Propagation Directions. Issue 7 (26th July 2019) - Gabrielse, Christine; Spanswick, Emma; Artemyev, Anton; Nishimura, Yukitoshi; Runov, Andrei; Lyons, Larry; Angelopoulos, Vassilis; Turner, Drew L.; Reeves, Geoffrey D.; McPherron, Robert; Donovan, Eric
Abstract: The injection region's formation, scale size, and propagation direction have been debated throughout the years, with new questions arising with increased plasma sheet observations by missions like Cluster and THEMIS. How do temporally and spatially small‐scale injections relate to the larger injections historically observed at geosynchronous orbit? How to account for opposing propagation directions—earthward, tailward, and azimuthal—observed by different studies? To address these questions, we used a combination of multisatellite and ground‐based observations to knit together a cohesive story explaining injection formation, propagation, and differing spatial scales and timescales. We used a case study to put statistics into context. First, fast earthward flows with embedded small‐scale dipolarizing flux bundles transport both magnetic flux and energetic particles earthward, resulting in minutes‐long injection signatures. Next, a large‐scale injection propagates azimuthally and poleward/tailward, observed in situ as enhanced flux and on the ground in the riometer signal. The large‐scale dipolarization propagates in a similar direction and speed as the large‐scale electron injection. We suggest small‐scale injections result from earthward‐propagating, small‐scale dipolarizing flux bundles, which rapidly contribute to the large‐scale dipolarization. We suggest the large‐scale dipolarization is the source of the large‐scale electron injection region, such that as dipolarization expands, so does the injection. The >90‐keV ion flux increased and decreased with the plasma flow, which died at the satellites as global dipolarization engulfed them. We suggest the ion injection region at these energies in the plasma sheet is better organized by the plasma flow. Plain Language Summary: During space weather events, energetic particles are transported toward the Earth and can populate the radiation belts. It is important to understand how these particles are being energized and transported so that we can understand the near‐Earth radiation environment better in order to protect astronauts and space‐borne assets. Previous studies showed competing evidence regarding the region where particles are energized and transported. Some studies showed that this region is wide and propagates toward the Earth. Other studies agreed that the region propagates toward the Earth but showed that the region is narrow. Yet other studies showed evidence that the region expands away from the Earth. Our work utilizes the Heliophysics/Geospace Systems Observatory—comprised of multiple spacecraft and ground‐based instrumentation like aurora cameras—to show that these competing results are actually different parts of the same space weather phenomenon. We show that the narrow, earthward‐propagating energization regions pile up near the Earth and contribute to the large energization region. This large energization region expands westward (making it wider) and away from the Earth. There is also evidence of the large energization region propagating toward the Earth, meaning it expands in all directions. Key Points: We use the extensive Heliophysics/Geospace Systems Observatory of ground‐ and space‐based data to study small‐ and large‐scale injections Electron injection evolution is correlated with Bz enhancements: small‐scale injections are related to DFBs, large‐scale injections to global dipolarization Ion injection evolution at satellite is correlated with enhanced plasma flow and electric field presence at the satellite